2014
DOI: 10.1007/s10329-014-0429-z
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the number of proximal caudal vertebrae with tail reduction in Old World monkeys

Abstract: Tail length in primates can vary greatly between species or even between local conspecific populations, and the tail is markedly reduced in several lineages. In Old World monkeys, tail length is considered as an important feature reflecting their phylogeny and adaptations. The number of caudal vertebrae is one of the important factors which determine tail length, and it is known that this number varies with tail length. Caudal vertebrae can be divided into two types (proximal and distal), and tail mobility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Proximal vertebrae have transverse processes and a spinous process, on which tail muscles insert, and consist of the main part of tail movement (swing). For these reasons previous studies focused on the number or length of the proximal caudal vertebrae and/or the morphology of the sacrum to find parameters that help estimate (reconstruct) the tail length 16,20,33 . However, our results showed the number and length of caudal vertebrae in the distal region varied more than the proximal region, and correlate more strongly with RTL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Proximal vertebrae have transverse processes and a spinous process, on which tail muscles insert, and consist of the main part of tail movement (swing). For these reasons previous studies focused on the number or length of the proximal caudal vertebrae and/or the morphology of the sacrum to find parameters that help estimate (reconstruct) the tail length 16,20,33 . However, our results showed the number and length of caudal vertebrae in the distal region varied more than the proximal region, and correlate more strongly with RTL.…”
Section: Discussionmentioning
confidence: 99%
“…Primates’ vertebrae are categorized into three types: proximal, transition, and distal 8,1820 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tojima (2014) revealed that the number of proximal caudal vertebrae, which provide insertion places to caudal muscles, correlated with relative tail length (the percentage of tail length against head and body length) in Papionini. Together with this insight, the result of this study suggested a possibility that the number of proximal caudal vertebrae and the insertion places of caudal muscles are highly related.…”
Section: Correlation Between the Variation Of Caudal Muscle Attachmenmentioning
confidence: 99%